The Myth of the Codes: Exploring Self-Built Rules in Peri-Urban Villages, Southern China - Wu, Jiong (International Planning History Society Proceedings, 2024)
This paper challenges the prevailing belief that informal settlements lack effective zoning and building regulations by presenting an ethnographic study on self-built practices in multiple peri-urban villages in the Guangzhou metropolis, Southern China, from 2012 to 2019. Under China’s urban-rural divided system, not only do formal urban zoning codes and building regulations not apply to these locales, but the emerging village regulatory frameworks are also often sites of contestation between the local state and residents. The research highlights how three distinct social groups within these villages have formulated their own informal self-built rules, akin to zoning and building codes. Local villagers have negotiated with their neighbours to establish rules on setbacks and patio arrangements to reduce overcrowding, enhance ventilation and natural lighting, and be competitive in the rental market. Peasant-workers, who fulfil dual roles as both builders and tenants, have improved housing standards by making on-site ad hoc adjustments to building elements like windows, balconies, patios, entrances, and staircases. Small businesspeople have established bottom-up guidelines to preserve and renovate traditional houses that are excluded from official preservation lists. This paper argues that these self-help settlements are not devoid of zoning and building regulations; rather, these communities develop their own sets of rules, albeit informally. Despite facing various limitations, these informal rules are crucial for grassroots empowerment. They use these rules to enhance their living conditions, establish collective actions, and leverage their economic and social interests. By revealing the rationales, mechanisms, and outcomes of these self-initiated rules, this study calls for a deeper reflection on how zoning and building codes could be made more effective and just in informal settlements.